Systems Practice: How to Act in a Climate-Change World - Ison, Ray.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2010)
It is now accepted that humans are changing the climate of the Earth and this is the most compelling amongst a long litany of reasons as to why, collectively, we have to change our ways of thinking and acting. Most people now recognise that we have to be capable of adapting quickly as new and uncertain circumstances emerge: this capability will need to exist at personal, group, community, regional, national and international levels, all at the same time. Systems Practice is structured into four parts. Part I introduces the societal need to move towards a more systemic and adaptive governance against the backdrop of human-induced climate change. Part II unpacks what is involved in systems practice by means of a juggler metaphor; examining situations where systems thinking offers useful understanding and opportunities for change. Part III identifies the main factors that constrain the uptake of systems practice and makes the case for innovation in practice by means of systemic inquiry, systemic action research and systemic intervention. The book concludes with Part IV, which critically examines how systems practice is, or might be, utilised at different levels from the personal to the societal. The development of our capabilities to think and act systemically is an urgent priority and Systems Practice aims to show how to do systems thinking and translate that thinking into praxis (theory informed practical action) which will be welcomed by those managing in situations of complexity and uncertainty across all domains of professional and personal concern.
Thinking and Acting Differently -- and Rationale -- Systems Practice as Juggling -- Introducing Systems Practice -- Making Choices About Situations and Systems -- The Juggler: A Way to Understand Systems Practice -- Juggling the B-Ball: Being a Systems Practitioner -- Juggling the E-Ball: Engaging with Situations -- Juggling the C-Ball: Contextualising Systems Approaches -- Juggling the M-Ball: Managing Overall Performance in a Situation -- Systemic Practices -- Four Settings That Constrain Systems Practice -- Systemic Inquiry -- Systemic Action Research -- Systemic Intervention -- Valuing Systems Practice in a Climate-change World -- Valuing Systems Practice.
Keywords: Computer science; Social sciences -- Data processing; Information Systems; Environmental management; Computer Science; Computer Appl. in Social and Behavioral Sciences; Computers and Society; Management of Computing and Information Systems; Environmental Management